How should activity guidelines for young people be operationalised? - Waters Elizabeth; Hesketh Kylie; Wake Melissa; Ridley Kate; Olds Tim; Patton George; Williams Joanne (BMC, 2007)
Abstract Background If guidelines regarding recommended activity levels for young people are to be meaningful and comparable, it should be clear how they are operationalised. It is usually open to interpretation whether young people are required to meet activity and screen time targets (1) all days of the week, (2) on most days of the week, (3) on average across all days, or (4) whether compliance should be understood as the probability that a randomly selected young person meets the guidelines on a randomly selected day. This paper studies this question using data drawn from the Australian Health of Young Victorians study. Methods The subjects for this study were 885 13-19 year olds who recalled four days of activities using a computerised use-of-time instrument, the Multimedia Activity Recall for Children and Adolescents (MARCA). Daily minutes of moderate-to-vigorous physical activity (MVPA) and screen time were calculated. The prevalence of compliance to Australian guidelines (≥ 60 min/day of MVPA and ≤ 120 min/day of screen time outside of school hours) was calculated using the four methods. Results The four methods resulted in significantly different prevalence estimates for compliance to the MVPA guideline (20-68%), screen guideline (12-42%) and both guidelines (2-26%). Furthermore, different individuals were identified as compliant by the different methods. Conclusion Clarification of how compliance to guidelines should be operationalised would assist in comparisons between studies, and in consistency in determining correlates of compliance.